2021
DOI: 10.52939/ijg.v17i1.1701
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Accuracy Assessment of Open Access Digital Elevation Models Using GPS

Abstract: In this study, the vertical accuracy of the Shuttle Radar Topography Mission Digital Elevation Model Version 2.0 (SRTM30), the Advanced Spaceborne Thermal Emission and Reflection Radiometer Global DEM Version 2.0 (ASTER GDEM2), and Advanced Land Observing Satellite World 3D Digital Surface Model Version 2.1 (ALOS AW3D30) was statistically assessed using GPS data. The Tashkent geodynamical polygon was chosen as a study region, where the land surface can reflect as both natural (tectonic) and man-made (Charvak r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…(13) AW3D30: The ALOS Global Digital Surface Model (DSM) "ALOSWold3D-30m" is a highprecision global digital terrain model DSM made freely available by the Japan Aerospace Exploration Agency in May 2016; it has a horizontal resolution of 30 m (1 arcsecond) and is generated from images with a resolution of 5 m. The AW3D30 DEM was developed using millions of images acquired using a panchromatic optical sensor (PRISM) on the ALOS satellite. (14) The first version of AW3D30 was released in May 2016, and new versions have been successively released. The latest version improves the absolute and relative accuracies through additional calibration and gap filling.…”
Section: Demmentioning
confidence: 99%
“…(13) AW3D30: The ALOS Global Digital Surface Model (DSM) "ALOSWold3D-30m" is a highprecision global digital terrain model DSM made freely available by the Japan Aerospace Exploration Agency in May 2016; it has a horizontal resolution of 30 m (1 arcsecond) and is generated from images with a resolution of 5 m. The AW3D30 DEM was developed using millions of images acquired using a panchromatic optical sensor (PRISM) on the ALOS satellite. (14) The first version of AW3D30 was released in May 2016, and new versions have been successively released. The latest version improves the absolute and relative accuracies through additional calibration and gap filling.…”
Section: Demmentioning
confidence: 99%
“…In earlier studies, the accuracy of DEMs, such as SRTM, ASTER GDEM, and ALOS PALSAR, was assessed using various data (DEMs of higher resolution, the utilization of Differential Global Positioning System (DGPS), terrestrial measurements (Bakiev & Khasanov, 2021). It was revealed that for the territories located near the reservoirs, ASTER DEM gives a more realistic representation of steep slopes and mountain ridges compared to SRTM or ALOS (Fazilova et al, 2021). The goal of this study is to quantify and compare the vertical accuracy of open access DEMs obtained using the Shuttle Radar Topography Mission (SRTM30), Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER GDEM2), and Advanced Land Observing Satellite (ALOS AW3D30) for the territory of the Fergana Valley in the Republic of Uzbekistan.…”
Section: Introductionmentioning
confidence: 99%